DiverCIAT - Andreea Nowak, Environmental Policy Specialist - International Center for Tropical Agriculture (2016)
CIAT Environmental Policy Specialist Andreea Nowak discusses growing up in rural Romania and how that led her to a career in development, where she focuses on helping countries make climate change a priority.